2019
DOI: 10.1021/acsnano.8b06795
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Radiosensitizing and Photothermal Performance of Cu2–xSe Nanocrystals for Synergetic Radiophotothermal Therapy of Orthotopic Breast Cancer

Abstract: The small difference between tumor and normal tissues in their responses to ionizing radiation has been a significant issue for radiotherapy of tumors. Herein, we report that dumbbell-shaped heterogeneous copper selenide-gold nanocrystals can serve as an efficient radiosensitizer for enhanced radiotherapy. The mean lethal dose of X-rays to 4T1 tumor cells can be drastically decreased about 40%, that is, decreasing from 1.81 to 1.10 Gy after culture with heterostructures. Due to the synergetic effect of heteros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(122 citation statements)
references
References 55 publications
4
114
0
Order By: Relevance
“…The temperature profiles of all these GNR@Cu 2-x Se heterostructures almost remain unchanged after five cycles of consecutive laser on/off irradiation, suggesting the high photothermal stability of these materials. Thus, we conclude that all these GNR@Cu 2-x Se heterostructures have excellent NIR-II photothermal performance with the η value ranging from 58-85% consistent with previously reported η values in the literature 26 , 58 - 60 , highlighting their potential as durable photothermal agents for NIR-II photothermal tumor ablation.…”
Section: Resultssupporting
confidence: 90%
“…The temperature profiles of all these GNR@Cu 2-x Se heterostructures almost remain unchanged after five cycles of consecutive laser on/off irradiation, suggesting the high photothermal stability of these materials. Thus, we conclude that all these GNR@Cu 2-x Se heterostructures have excellent NIR-II photothermal performance with the η value ranging from 58-85% consistent with previously reported η values in the literature 26 , 58 - 60 , highlighting their potential as durable photothermal agents for NIR-II photothermal tumor ablation.…”
Section: Resultssupporting
confidence: 90%
“…On this ground, the heterogeneous copper selenide‐Au (CSA) nanoparticles with dumbbell morphology were synthesized as both radiosensitizer and photothermal nanoagent for synergistic RT and PTT against tumor ( Figure a), in accompany with triple‐diagnostic imaging capability by labeling with radioactive 99m Tc (SPECT, PA, and CT). [ 203 ] Such a synergistic performance was much profound as compared to either Cu 2− x Se nanocrystals or Au nanoparticles, and even the Cu 2− x Se/Au mixture, which was signified by improved tumor‐suppressing efficiency (Figure 24b) and survival rate (Figure 24c) of tumor‐bearing mice. The tumor metastasis into the lung was also decreased by synergistic RT and PTT (Figure 24d).…”
Section: Cu‐involved Nanoagents For Synergistic Nanotherapeuticsmentioning
confidence: 99%
“…As ac ontrol, the temperature of the UiO-66-N 3 dispersion ( Figure S9) or pure deionized water showed negligible increase under the same irradiation conditions, which revealed that free MOF and laser irradiation alone would cause minimal thermale ffects.F inally,t he photothermal stability of the NP dispersion in response to photoexcitation was examined. [19] The DOX release behavior of UiO-Ra-DOX-CuS was investigated in PBS at different pH values (5.0 and 7.4). Ac onsistent limit temperature was observed, indicating the remarkable photothermal stability of UiO-Ra-DOX-CuS NPs.…”
Section: Resultsmentioning
confidence: 99%